Fire retardancy of natural fibers: Mechanisms, treatments, and testing methods - Sawsan Dagher; Boshra Akhozheya; Ali Abu Odeh; Raghad Alyafei; Anood Ahli; Shamsa Alzaabi; Maha Almansoori; Fatima Alhashmi (Hybrid Advances, 2025)
Natural fibers are increasingly recognized as sustainable alternatives to synthetic fibers in various industries due to their biodegradability and renewability. However, their inherent flammability limits their application in fire-sensitive areas. This review provides a comprehensive overview of fire retardancy mechanisms, methods for enhancing fire resistance, and fire retardant testing protocols for natural fibers. It addresses the combustion behavior of natural fibers, focusing on the roles of cellulose, hemicellulose, and lignin, and explores chemical treatments such as phosphorus-based compounds, bio-based coatings, boron-based additives, and silicon-based fire retardants. Physical and structural modifications, including surface coatings and hybrid fiber reinforcement, are also discussed. Key fire testing protocols, including Limiting Oxygen Index (LOI), Cone Calorimetry, Thermogravimetric Analysis (TGA), and UL-94, are reviewed, along with studies demonstrating the efficacy of various fire retardant treatments. Finally, the review identifies future research directions, such as the design of biodegradable flame retardants and the industrial scalability of sustainable treatments.